Injectable and Assembled Calcium Sulfate/Magnesium Silicate 3D Scaffold Promotes Bone Repair by In Situ Osteoinduction - Wei Zhu; Tianhao Zhao; Han Wang; Guangli Liu; Yixin Bian; Qi Wang; Wei Xia; Siyi Cai; Xisheng Weng (Bioengineering)
(1) Background: Osteonecrosis of the femoral head (ONFH), caused by insufficient blood supply, leads to bone tissue death. Current treatments lack effective bone regeneration materials to reverse disease progression. This study introduces an injectable and self-setting 3D porous bioceramic scaffold (Mg@Ca), combining MgO + SiO2 mixtures with α-hemihydrate calcium sulfate, designed to promote bone repair through in situ pore formation and osteoinduction. (2) Methods: In vitro experiments evaluated human bone marrow mesenchymal stem cell (h-BMSC) proliferation, differentiation, and osteogenic marker expression in Mg@Ca medium. Transcriptome sequencing identified bone development-related pathways. In vivo efficacy was assessed in a rabbit model of ONFH to evaluate bone repair. (3) Results: The Mg@Ca scaffold demonstrated excellent biocompatibility and supported h-BMSC proliferation and differentiation, with significant up-regulation of COL1A1 and BGLAP. Transcriptome analysis revealed activation of the PI3K-Akt signaling pathway, critical for osteogenesis. In vivo results confirmed enhanced trabecular density and bone volume compared to controls, indicating effective bone repair and regeneration. (4) Conclusions: The Mg@Ca scaffold offers a promising therapeutic approach for ONFH, providing a minimally invasive solution for bone defect repair while stimulating natural bone regeneration. Its injectable and self-setting properties ensure precise filling of bone defects, making it suitable for clinical applications.